Factors associated with the formation of neutralizing antibodies post-vaccination: a lesson from COVID-19 vaccination - Hana Ratnawati; Fen Tih; Grace Puspasari; Allen A. Pelapelapon; Steven Felim (Exploration of Immunology)
Aim: This study aims to identify the factors affecting the formation of neutralizing antibodies (NAbs) in healthy adults four weeks post-COVID-19 vaccination. Methods: A cross-sectional study was conducted among mass vaccination attendees using inactivated CoronaVac. Collected the peripheral blood serum four weeks following the second vaccine dose. Forty-four adults aged 26–85 were split into two groups based on age (≤ 60 years and > 60 years) and BMI (non-obese ≤ 25 kg/m2 and obese > 25 kg/m2). Variables like age, gender, BMI, and the presence of comorbidities were recorded. CD4/CD8 ratio and vitamin D levels were examined for their influence on NAbs formation. NAbs were measured using ELISA, T-cells via flow cytometry, and vitamin D through radioimmunoassay. Descriptive data analysis was performed as mean ± standard deviation to show the characteristics of the sample. Students’ t-tests and multivariate and univariate regression analyses were used to evaluate the data. Results: Significant variations in NAbs levels were observed with age (P = 0.013), BMI (P = 0.004), and comorbidities (P = 0.034). The elderly demonstrated higher NAb levels, potentially due to the high vitamin D levels compared to the adult group. The vitamin D levels strongly correlated with NAb titer (P < 0.001; R = 0.843). A collective correlation was found between NAb levels and the factors of age, BMI, and CD4/CD8 ratio (P = 0.033). A negative correlation existed between BMI and NAb levels (P = 0.018; R = –0.356) and between age and the CD4/CD8 ratio (P = 0.440; R = –0.119), but age alone did not correlate with NAb titer. Conclusions: Age, BMI, CD4/CD8 ratio, and comorbidities influence the production of post-vaccination NAbs. Sufficient vitamin D levels in the elderly significantly boost post-vaccination NAb levels. Maintaining a healthy body weight is also vital, as studies have revealed a significant and negative correlation between BMI and the level of NAbs, suggesting a possible need for adjusted vaccine doses in obese individuals.